(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The research examines the degree of instructors’ overall commitment and the level of commitment in each of the three categories of organizational commitment. In this ex-post facto study, descriptive statistics are used to examine the data. Overall, teachers’ commitment to official tasks is quite strong, and it’s also high across all three aspects of organization commitment. However, it recommends that the government provide funds for teacher training and retraining in order to meet the challenges of ongoing economic and social reforms at a time when State and national resources are diminishing in order to maintain and possibly improve on this high level of commitment among teachers to their duties and to the schools. Our research population comprises of 204 instructors and 380 students of the qualifying secondary level in 29 local public schools of the qualifying secondary cycle in Tangier-Assilah Provincial Directorate of National Education (Morocco). Through the use of an empirical research, our findings reveal that the level of student participation in local public secondary schools in Tangier-Provincial Asimah’s Directorate of National Education is positively and statistically significant linked to student academic accomplishment (Morocco).